Cu and/or Ni catalysts over CePr oxide for the water gas shift reaction: an experimental study, kinetic fitting and reactor simulation - Poggio Fraccari, Eduardo Arístides (2017)
Several Cu and Ni samples, supported over Pr-promoted ceria, were characterized and tested as water gas shift (WGS) catalysts in the temperature range 250–450 °C. Three metal loadings were studied, 5, 10 and 20 wt%. Redox (TPR) and textural (XRD and BET) properties were correlated with the observed catalytic behavior. The activity clearly increased with metal loading (Cu or Ni) from 5 to 10 wt%, but no major changes were observed between mid and high metal loading samples, 10 and 20 wt%. This might be due to appreciable metal segregation over support surface as Cu or Ni content increases. For Ni-containing samples, CH4 was found at the reactor outlet stream, showing that CO methanation also takes place. For 10 wt% total metal content, kinetic expressions for monometallic Cu and Ni catalysts, and a bimetallic CuNi were proposed and fitted simultaneously for both WGS and the CO methanation reaction. Then, the kinetic expressions were used to model a reactor scheme where the main goal was the minimization of the required catalyst mass for a given CO conversion. It can be concluded that the most promissory scheme consists of two reactors, the first operating with the CuNi catalyst at high temperature and the second with the Cu catalyst at a lower temperature.